2018
DOI: 10.1159/000488179
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Receptor-Interacting Protein Kinase-1 in Neutrophil Extracellular Trap Formation in Patients with Systemic Lupus Erythematosus: a Preliminary Study

Abstract: Background/Aims: Neutrophil extracellular traps (NETs) are known to play an important role in systemic lupus erythematosus (SLE) by triggering innate and adaptive immune responses. The molecular mechanisms responsible for their formation in SLE are still unclear. In this study, we aim to characterize the role of the receptor-interacting protein kinase-1 (RIPK1), a homologous serine/threonine kinase previously implicated in the regulation of necroptosis and tissue injury, in decreasing neutrophil death and form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…They can kill pathogens by chemotaxis, phagocytosis, and direct sterilization [30]. In recent years, neutrophil extracellular trap (NET), a new neutrophil antibacterial method, has been discovered, which can not only capture and kill pathogens by releasing nucleic acid substances and granulocyte proteins into a network structure but also is related to multiple pathophysiological processes of human body, such as inflammation, tumor cell migration, ischemia/ reperfusion injury, autoimmunity [31][32][33], etc. It is noteworthy that neutrophils mediate the inflammatory response in kidney injury by various biochemical mechanisms, leading to further tissue damage [34].…”
Section: Discussionmentioning
confidence: 99%
“…They can kill pathogens by chemotaxis, phagocytosis, and direct sterilization [30]. In recent years, neutrophil extracellular trap (NET), a new neutrophil antibacterial method, has been discovered, which can not only capture and kill pathogens by releasing nucleic acid substances and granulocyte proteins into a network structure but also is related to multiple pathophysiological processes of human body, such as inflammation, tumor cell migration, ischemia/ reperfusion injury, autoimmunity [31][32][33], etc. It is noteworthy that neutrophils mediate the inflammatory response in kidney injury by various biochemical mechanisms, leading to further tissue damage [34].…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry validation. Established panels (Supplemental Table 1) and protocols were used as described previously (53). Briefly, cells were blocked with Fc block in staining buffer for 10 minutes at room temperature, incubated with antibodies in staining buffer for 30 minutes at 4°C, and then washed twice with staining buffer.…”
Section: Methodsmentioning
confidence: 99%
“…qPCR. Protocols were employed as described previously (53). Total RNA from human PBMCs was isolated using TRIzol according to the manufacturer's instructions (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, antiribonucleoprotein antibodies in SLE patients can also induce neutrophils in SLE patients to secrete NETs, further activating pDCs to release proinflammatory factors, such as IFN-α and IL-6 [111]. Guo et al [112] further confirmed that neutrophils derived from SLE patients were more likely to form NETs when stimulated by external stimuli, and SLE patients have a higher levels of IFN-α. In addition, neutrophil intracellular MMP-9 is externalized during NET formation, and MMP-9 induces endothelial dysfunction by activating MMP-2, which participates in the SLE disease process [18].…”
Section: Nets and Autoimmune Diseasesmentioning
confidence: 97%